Line profiles and magnetic fields in the exclusively powerful solar flare of October 28, 2003: preliminary results - Lozitsky, V.G.; Lozitska, N.I. (Кинематика и физика небесных тел, 2005)
We investigate the X17.2/4B solar flare of October 28, 2003 which has been occupying the third place among X-ray fluxes since 1975. The echelle Zeeman spectrograms obtained at the Kyiv University Astronomical Observatory allow us to conclude the following: a) observed flare emission in some magnetosensitive metallic lines can produce a false magnetographic signal of opposite polarity in case of Babcock’s or filter magnetograph, b) considerable both horizontal and vertical magnetic field inhomogeneity existed in the flare. The longitudinal mean magnetic field strength B|| was maximal at chromospheric level, which follows from a comparison of data in the Fe I λ 630.25 nm, He I D3, NaI D1 and D2 lines. In particular, the line ratios B||(D2)/B||(630.25) ≈ 3.2 and B||(D3)/B||(630.25) ≈ 2.0 were derived.